Evaluasi Kesesuaian Lahan Untuk Tanaman Cengkeh (Eugenia Aromatica L) di DAS Takapala Sub DAS Hulu Jeneberang Kabupaten Gowa - Iswan, Iswan; Zhiddiq, Sulaiman; Maru, Rosmini (UNM Geographic Journal, 2019)
ABSTRACT This study aims to determine: 1) land characteristics in the Takapala Watershed, Jeneberang Hulu Sub Watershed, Gowa Regency, 2) Land suitability for clove plants, 3) land suitability distribution for clove plants in Takapala Watershed, Jeneberang Hulu Sub Watershed, Gowa Regency. The method used is purposive sampling with data analysis techniques, namely matching techniques. The results showed: 1) the characteristics of the land in the Takapala watershed, the Jeneberang Upper Watershed, which is located in a slightly wet climate area; tempereture or air temperature is in hot / tropical regions; the availability of water for rainfall is rather wet; the availability of water for the dry month is quite suitable; rooting media for good to rather good soil drainage; soil texture from clay to clay clay; effective depth in; nutrient retention for medium to high CEC; acidic soil pH to slightly acidic; nutrients available for P2O5 (P available) low; potential mechanism for slopes from flat, gentle, slightly gentle / steep, steep and very steep; outcrops of rock did not exist until a little. 2) The level of land suitability for clove plants in the Takapala watershed in the Jeneberang Upper Watershed obtained five land suitability sub-classes, namely S2, quite in accordance with an area of 93.95 Ha; S3 - W1 (class according to marginal with the heaviest limiting factor of rainfall) with 1022.33 Ha; S3 - S1 (suitable class marginal with the heaviest limiting factor) with an area of 510.66 Ha; S3 - W1s1 (class suitable marginal with the heaviest limiting factor of rainfall and slope) with an area of 256.49 Ha, and N1 - S1 (class not suitable for now with a very severe limiting factor is the slope) with an area of 222.64 Ha. 4) Land suitability distribution for clove plants in the Takapala watershed, Jeneberang Upper Watershed is divided into three classes. class S2 (quite suitable) with an area of about 93.95 Ha or 4.41% of the Takapala watershed area; S3 class (according to marginal) with an area of around 1789.48 or 84% of the Takapala watershed area; and class N1 (not suitable for now) with an area of around 222.64 Ha or 10.45% of the total area of the Takapala River Basin.ABSTRAKPenelitian ini bertujuan untuk mengetahui: 1) karakteristik lahan di DAS Takapala Sub DAS Hulu Jeneberang Kabupaten Gowa, 2) Tingkat kesesuaian lahan untuk tanaman cengkeh, 3) agihan kesesuaian lahan untuk tanaman cengkeh di DAS Takapala Sub DAS Hulu Jeneberang Kabupaten Gowa. Metode yang digunakan adalah Purposive Sampling dengan teknik analisis data yaitu teknik matching. Hasil penelitian menunjukkan: 1) karakteristik lahan di DAS Takapala Sub DAS Hulu Jeneberang yaitu berada pada daerah iklim agak basah; temperatur atau suhu udara berada pada daerah panas/tropis; ketersedian air untuk curah hujan agak basah; ketesedian air untuk bulan kering cukup sesuai; media perakaran untuk drainase tanah baik sampai agak baik; tekstur tanah dari liat sampai lempung berliat; kedalaman efektif dalam; retensi hara untuk KTK tanah sedang sampai tinggi; pH tanah asam hingga agak asam; hara tersedia untuk P2O5 (P tersedia) rendah; potensi mekanisme untuk lereng dari datar, landai, agak landai/miring, curam, dan sangat curam; singkapan batuan tidak ada sampai sedikit. 2) Tingkat kesesuian lahan untuk tanaman cengkeh di DAS Takapala Sub DAS Hulu Jeneberang diperoleh lima sub kelas kesesuaian lahan yaitu S2 cukup sesuai dengan luas 93,95 Ha; S3 - W1 (kelas sesuai marginal dengan faktor pembatas terberat curah hujan) dengan 1022,33 Ha; S3 - S1 (kelas sesuai marginal dengan faktor pembatas terberat lereng) dengan luas 510,66 Ha; S3 - W1s1 (kelas sesuai marginal dengan faktor pembatas terberat curah hujan dan lereng)Â  dengan luas 256,49 Ha, dan N1 - S1 (kelas tidak sesuaiÂ  untuk saat ini dengan faktor pembatas sangat berat adalah lereng) dengan luas 222,64 Ha. 4)Agihan kesesuaian lahan untuk tanaman cengkeh di DAS Takapala Sub DAS Hulu Jeneberang terbagi menjadi tiga kelas. kelas S2 (cukup sesuai) dengan luas sekitar 93,95 Ha atau 4,41 % dari luas DAS Takapala; kelas S3 (sesuai marginal) dengan luas sekitar 1789,48 atau 84 % dari luas DAS Takapala; dan kelas N1 (tidak sesuai untuk saat ini) dengan luas sekitar 222,64 Ha atau 10,45% dari luas keseluruhan DAS Takapala.